Pomegranate seed extract enhances the inhibitory effect of adipose- derived mesenchymal stem cells on breast cancer cell line in co-culture conditions - Nahid Moradi-Gharibvand; Mohsen Setayeshmehr; Mohammad Kazemi; Azadeh Safaee; Laya Sadat Khorsandi; Darioush Bijan Nejad; Seyed Javad Hasheminia; Batool Hashemibeni (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Pomegranate seed extract (PSE) possesses anticancer activities and healing effects. Adipose-derived stem cells (ADSCs) are being considered a new candidate for cancer treatment. The purpose of this study was to investigate the effect of PSE on the cell cycle and apoptosis of the MCF-7 cell line in the co-culture condition with ADSCs. Experimental approach: MCF-7 and ADSC cells (ratio 1/1) were cultured in a transwell plate with and without PSE (PSE-co-culture and co-culture groups). MCF-7 cells were cultured in monolayer without and with PSE (mono-culture and PSE-mono-culture groups). MCF-7 cell line was harvested on day 5 and cell viability, apoptotic activity, cell cycle, and gene expression were evaluated. Findings / Results: The results of the MTT assay indicated that PSE at 100 μg/mL has the highest cytotoxicity on the MCF-7 in the PSE-co-culture group. The cell cycle analysis revealed that ADSCs in combination with PSE significantly increased the population of MCF-7 cells in the G1 phase, resulting in the arrest of MCF-7 cells cycle in the G0/G1 transition. In addition, the most apoptotic MCF-7 cells (41.5%) were detected in the same group. Expression of BAX and caspase3 genes were upregulated while anti-apoptotic (BCL-2) and angiogenesis inducer (VEGF) genes were downregulated in the PSE-co-culture group compared with the other groups. Conclusion and implications: ADSCs reduced cell viability and proliferation of MCF-7 cells in co-culture conditions and adding PSE to the medium increased the apoptosis of cancer cells. This study suggests that ADSCs with PSE can suppress tumor cells.